2004
DOI: 10.1002/cjg2.3547
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation and Hysteresis of Saturated Rocks Under Cyclic Loading

Abstract: Hysteresis such as stress‐strain loop, “X” shape of instantaneous modulus and Poisson's ratio, and effect of strain amplitude on attenuation of saturated rocks is analyzed under cyclic loading with experiments of fluid saturated sandstones and marbles. We think that the attenuation of rock is in proportion to the strain amplitude of the applied cyclic loading, and the b value of attenuation is a measurement of saturated rock's attenuation under cyclic loading. We discuss the possible micro mechanisms of attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…From Figs 8 and 9, it is observed that the curves of ΔU d and Δε p show some fluctuation in each cycle stage before the destruction stage; this phenomenon has also been found in other studies [38][39][40][41][42]. There are many explanations for this phenomenon, but it is generally accepted that a rock mass is composed of micro-structural elements (see Fig 10).…”
Section: Fluctuations Of δε P and δU D Under Tiered Cyclic Loadingsupporting
confidence: 70%
See 1 more Smart Citation
“…From Figs 8 and 9, it is observed that the curves of ΔU d and Δε p show some fluctuation in each cycle stage before the destruction stage; this phenomenon has also been found in other studies [38][39][40][41][42]. There are many explanations for this phenomenon, but it is generally accepted that a rock mass is composed of micro-structural elements (see Fig 10).…”
Section: Fluctuations Of δε P and δU D Under Tiered Cyclic Loadingsupporting
confidence: 70%
“…When the cyclic stress reaches the failure strength limit of each micro-structural element, local failure occurs and the residual deformation of rock suddenly increases [9,23]. However, other researchers believe that sandstone subjected to cyclic stress displays complex stress-strain characteristics of nonlinearity and hysteresis, owing mainly to nonlinear deformations and the frictional sliding of grain contacts [40][41][42]. The phenomenon of unstable deformation (or unstable damage) of sandstone exactly reflects that sandstone is a natural product of heterogeneity and anisotropy [43,44].…”
Section: Fluctuations Of δε P and δU D Under Tiered Cyclic Loadingmentioning
confidence: 99%
“…As a natural geological material, rock has a large number of microcracks, pores and other inner defects. The microstructure characteristic of rock results in its nonlinear elastic behavior and significant hysteresis behavior (Chen et al 2003;Li et al 2019). The hysteresis curves of the stress-strain and stress-variance at different stress levels are shown in Fig.…”
Section: Variance Response Characteristicsmentioning
confidence: 99%
“…At the lower loading frequency of 0.05 Hz, the dynamic strength of all cracked samples were lower than their static strength, except for the T-shaped fissure samples of 0 °-90 °and 45 °-90 °(see Figures 11B,C). Because of the working condition of lower frequency and the cycle period is longer than the hysteresis time (e.g., Chen et al, 2004;Wan and Xi. 2009), the strain has sufficient reaction time.…”
Section: Strength Characteristics Under Different Frequenciesmentioning
confidence: 99%